UPAYA PENCEGAHAN HIV-AIDS MELALUI PENYULUHAN KESEHATAN UNTUK MENINGKATKAN PENGETAHUAN SISWA SMK FARMASI KABUPATEN SUMBAWA - Nur Arifatus Sholihah; Asri Reni Handayani; Galuh Permatasari (Midwifery Care Journal, 2022)
HIV-AIDS is a sexually transmitted disease whose appearance is like an iceberg phenomenon, namely the number of reported sufferers is much smaller than the actual number of sufferers. The spread of HIV-AIDS is strongly influenced by factors of education, knowledge, attitudes and behavior. The provision of information is expected to increase knowledge and can be done by providing sosializaton to the community, group or individual. This study aims to prove that HIV-AIDS counseling has an effect on the level of knowledge about HIV/AIDS. The design of this study was a pre and post test group, involving 30 students of Pharmacy Vocational School in Sumbawa Regency, which were selected using simple random sampling technique. The mean level of knowledge of students before counseling was 12.03 and after counseling was 17.97. The p-value of the t-test is 0.0001, thus it is interpreted that counseling has an effect on the level of knowledge of students about HIV/AIDS at the Pharmacy Vocational School of Sumbawa Regency. Thus, it is important to increase knowledge and understanding of how to prevent and treat HIV Aids, especially among adolescents through sosialization about HIV Aids.